Training and Mentoring on Developing Critical Thinking Assessment Instruments for Islamic Civilization History Teachers in Madrasah Aliyah - Budi Santoso; Mukhlas Triono; Febrian Andi Hidayat (CV. Dharma Samakta Edukhatulistiwa, 2026)
The limited competence of Islamic Civilization History teachers in developing critical thinking assessment instruments remains a significant challenge in implementing the Merdeka Curriculum. Most teachers continue to use assessment practices that emphasize lower-order thinking skills and have limited understanding of the Facione critical thinking framework. This community service program aimed to strengthen teachers' competence through training and mentoring using the Participatory Action Learning (PAL) approach, which was selected to promote active participation, collaborative problem-solving, and continuous practice in authentic assessment development. The program involved 15 Islamic Civilization History teachers from six Madrasah Aliyah in Sorong Regency, Southwest Papua. Program effectiveness was evaluated through pre-test and post-test assessments, observations, and product evaluations. The results showed a substantial improvement in teachers' competence, with the mean score increasing from 61.33 to 87.13, representing an improvement of 42.07%. All participants successfully developed classroom-ready assessment packages consisting of assessment blueprints, HOTS-based test items, scoring rubrics, and assessment formats aligned with the six critical thinking dimensions proposed by Facione. Product evaluation further indicated that the developed instruments were relevant, practical, and suitable for classroom implementation. These findings demonstrate that the PAL-based training and mentoring model effectively enhances teachers' assessment literacy while producing validated assessment instruments that support authentic assessment practices and strengthen the implementation of the Merdeka Curriculum in Madrasah Aliyah.